2005
DOI: 10.1111/j.1478-3231.2005.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemosiderosis is associated with accelerated decompensation and decreased survival in patients with cirrhosis

Abstract: The presence of siderosis is associated with more advanced liver dysfunction. Even when the effects of baseline liver function are taken into account, siderosis is associated with decreased survival and more rapid decompensation in cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…Nevertheless, iron was recently shown to inhibit the activity of HCV RNA dependent RNA polymerase (RdRP) as well as reducing replication in NS replicons (37). Our data clearly support these results, however, a potential antiviral role for iron must be considered in the context of clinical data showing that mild increases in storage iron correlate with progressive HCV liver disease and hepatic decompensation (38;39). Furthermore, a potential role for biliverdin and CO as inhibitors of viral replication through antioxidative behavior requires further study.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, iron was recently shown to inhibit the activity of HCV RNA dependent RNA polymerase (RdRP) as well as reducing replication in NS replicons (37). Our data clearly support these results, however, a potential antiviral role for iron must be considered in the context of clinical data showing that mild increases in storage iron correlate with progressive HCV liver disease and hepatic decompensation (38;39). Furthermore, a potential role for biliverdin and CO as inhibitors of viral replication through antioxidative behavior requires further study.…”
Section: Discussionsupporting
confidence: 84%
“…We recently reported that the presence of stainable iron on an index liver biopsy showing cirrhosis was associated with higher baseline MELD score. 2 Moreover, even when the more advanced degree of liver dysfunction in these patients was taken into account, they tended to decompensate more rapidly than patients without stainable iron. Ganne-Carrié et al 3 have made similar observations in patients with alcoholic cirrhosis.…”
mentioning
confidence: 99%
“…Iron would also be an unlikely choice as a therapeutic agent for HCV since it is usually considered to be a hepatotoxin (Ryter and Tyrrell, 2000) and it seems doubtful whether sufficient intracellular levels of free iron might be achieved in vivo to be useful therapeutically without causing cellular injury. Mild iron accumulation in HCV infected human liver samples has been correlated with more severe liver disease in some but not all studies (Beinker et al, 1996; Kayali et al, 2005, 2007). Some but not all earlier clinical studies with α-interferon treatment regimens suggested that phlebotomy could improve viral clearance and increase sustained virological responses to α-interferon (Di Bisceglie et al, 2000; Fontana et al, 2000; Desai et al, 2008).…”
Section: Direct Antiviral Effects Of Heme and Derivatives On Hcvmentioning
confidence: 98%